Pola Interaksi Pendidik dan Peserta Didik dalam Membentuk Pribadi Muslim di SMAN 1 Jangka Buya - Mursyidi, Mursyidi (Wasatha: Jurnal Studi Islam dan Humaniora, 2023)
The responsibilities of the Islamic Religious Education Teacher to Allah in the personal formation of students include regarding the truthfulness of the material presented and carrying out tasks in accordance with the main duties of a teacher. The results of this qualitative study show that the pattern of interaction between Islamic Religious Education teachers and students in shaping the personality of Muslims at SMAN 1 Term Buya, Pidie Jaya Regency, is through an approach in carrying out worship, extracurricular activities, the commemoration of Islamic Holidays (PHBI). The pattern of interaction that is built is that the teacher is sincere in behaving and acting and trying to understand the attitudes of students with all the consequences, so as to create a harmonious two-way relationship that has educational and religious value. The pattern of interaction between Islamic Religious Education teachers and students is carried out inside and outside the classroom, by taking a personalized approach to students, attracting students' interest in studying religion, through guidance in discipline and creativity, creating a conducive religious atmosphere, moral habituation education, and morals, the teacher is a good example for students, instills awareness in students that the obligation to carry out religious orders is a personal responsibility, the teacher works closely with the parents of students.